MULTIMEDIA INTERAKTIF BERBASIS COURSE LAB DALAM PEMBELAJARAN MEMAHAMI DASAR-DASAR ELEKTRONIKA - Fivia Eliza; Novi Pranata; Radinal Fadli (Jurnal Teknologi Informasi dan Pendidikan, 2019)
This research is motivated by One-way learning media using whiteboard media, presentation media such as power point media which causes students to decrease motivation to learn and improve student learning outcomes. The purpose of this study was to produce interactive multimedia products based on the Course Lab. This type of research is development research (Research and Development). This study uses the ADDIE Model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The results of the development obtained by interactive multimedia based on Course Lab and the results of the study obtained Interactive Multimedia-based Course Lab validation worth 4.12 with the valid category. Thus it can be used as learning media. The test results practicalities of the subject teachers and students of the Interactive Multimedia Course Based Lab obtained with a level of practicality of the subject teachers at 4,17 on the category of practical and student responses on the Interactive Multimedia obtained at 4,01 on Practical category. And the effectiveness of the use of Interactive Multimedia Based Course Lab obtained from students' classical mastery level is 87,5% of Minimum Criterion Criterion (KKM) of 80.